Self-assembled single-atom nanozyme for enhanced photodynamic therapy treatment of tumor - Dongdong Wang (Nature Portfolio, 2020)
The hypoxic microenvironment in solid tumors limits the efficacy of photodynamic therapy (PDT) since oxygen is necessary to produce high cytotoxic singlet oxygen species. Here, the authors develop an improved self-assembled single-atom nanozyme which allows oxygen generation to enhance PDT efficacy.